Exploring Satisfaction Towards Web Text Reading Among Dyslexic and Normal Learners - Chen, Chwen Jen; Keong, Melissa Wei Yin; Teh, Chee Siong; Chuah, Kee-Man (International Journal of Learning and Teaching, 2015)
The study aims to investigate the difference insatisfaction levels between normal and dyslexic learners when presented with various web text modes. Due to the high percentage of web users who exhibit some traits ofdyslexia, presenting a web text that follows the guidelines which are meant for normal users poses challenges todyslexic users. Acknowledging the ubiquitous use of the web for learning and the massive availability of text on the web as well as the significant number of dyslexic learners, this investigation intends to derive appropriate guidelines for displaying web text that could accommodate both normal and dyslexic learners. This qualitative study employs a multiple case study design and data are mainly collected via observation and guided interviews. The study reveals that existing dyslexia-friendly text guidelines are also appropriate for normal learners and contrary to the popular belief that assistive technology such as screen readers are helpful in reading, reading text aloud does not always work for both dyslexic and normal learners.